2009
DOI: 10.1254/jphs.09020fp
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Organobismuth(III) Compound Targets Tubulin to Induce G2/M Arrest in HeLa Cells

Abstract: Abstract. Our previous study showed that organobismuth compounds induce apoptosis in human promyelocytic leukemia cells, although solid tumor cell lines were relatively resistant. Herein, we investigated the primary cellular target of these compounds in HeLa cells. One organobismuth compound, bi-chlorodibenzo[c,f][1,5]thiabismocine (compound 3), arrested the cell cycle at G 2 /M as assessed by flow cytometry and by upregulating the expression of cyclin B1. At a low concentration (0.5 μM), compound 3 caused cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…Most antimicrotubule agents that target the cellular microtubule network result in an aberrant formation of the mitotic spindle, subsequent blockage of the cell cycle in G 2 /M phase and causing apoptotic cell death [20,21]. Since α-santalol caused G 2 /M phase arrest and apoptosis, we examined whether it affects the organization of microtubules in UACC-62 cells, which are relatively big cells and their microtubules are easily visualized compared to A431 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Most antimicrotubule agents that target the cellular microtubule network result in an aberrant formation of the mitotic spindle, subsequent blockage of the cell cycle in G 2 /M phase and causing apoptotic cell death [20,21]. Since α-santalol caused G 2 /M phase arrest and apoptosis, we examined whether it affects the organization of microtubules in UACC-62 cells, which are relatively big cells and their microtubules are easily visualized compared to A431 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Microtubule polymerization dynamics was monitored by measuring the change in absorbance at 340 nm every 1 or 5 min for 60 min at 37°C using a SmartSpec TM 3000 (Bio-Rad Laboratories, Hercules, CA, USA). As positive controls of the microtubule sensitizer, TAX and VNR were prepared, of which concentrations were set according to previous reports (31,32).…”
Section: In Vitro Microtubule Polymerization Assaymentioning
confidence: 99%
“…However, our preliminary experiments with heterocyclic organobismuth(III) using an in vitro assay system with GSH as substrate did not show any evidence of the direct inhibition of glutathione peroxidase activity. In addition, we have revealed that one specific biological target of heterocyclic organobismuth(III) is tubulin [24]. However, as shown in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The assembly of porcine tubulin was monitored using porcine brain tubulin purified as described earlier [24]. Tubulin was resuspended on ice in ice-cold tubulin-polymerization buffer (80 mM piperazine-1, 4-bis (2-ethane sulfonic acid (PIPES) pH 6.9, 2 mM MgSO 4 , 1 mM ethylene glycol tetra acetic acid (EGTA), 1 mM Mg-GTP, and 1.5% (v/v) glycerol) and 100 μl (250 μg) was pipetted into the designated wells of a half area 96-well plate pre-warmed to 25°C in 0.20 mM of each compound.…”
Section: Assay Of Microtubule Assembly In Vitromentioning
confidence: 99%
See 1 more Smart Citation